Nrl knockdown by AAV-delivered CRISPR/Cas9 prevents retinal degeneration in mice - Wenhan Yu (Nature Portfolio, 2017)
Retinitis pigmentosa is mainly caused by mutations that initially affect survival of rod photoreceptors, leading to secondary loss of cones. Here the authors use gene editing to prevent rod degeneration, leading to survival of cones and improved vision in mice.